Pertumbuhan Api-Api (Avicennia alba) dan Kelimpahan Epifauna Bentik di Kawasan Rehabilitasi Mangrove Desa Kedaburapat Kabupaten Kepulauan Meranti - Efriyeldi Efriyeldi; Aras Mulyadi; Joko Samiaji (Universitas Riau, 2021)
The research was conducted in July - October 2020. Collection of data A. alba growth and abundance of benthic epifauna was carried out in the mangrove rehabilitated area of Kedabupat village, Kepulauan Meranti Regency. The aims of this study was to analyze the growth (stems height and diameter) of the mangrove A. alba species as a result of rehabilitation and abundance of benthic epifauna in the area. The method used in this research was a survey method, where data was obtained by directly to the research location. The data collected was data on the height and diameter of A. alba stems, density of macro epifauna species, and water quality in the field, then followed by analysis of water and sediment samples in the laboratory. The results showed that the average increace in height of the stem by zone was 6.45-12.93 cm/month, meanwhile the average value of the increase in stem diameter by zone is 1.53-1.85 mm/month. There were 13 epifauna benthic species from 2 classes namely Gastropod and Malacostraca from mangrove rehabilitation. Gastropod class that was Littoraria melanostoma, Nerita balteata and Sphaerassiminea miniata; from the malacostraca class that was Uca coarctata, Metopograpsus latifrons, Ceonobita cavipes, and Clibanarius longitarsus. Benthic epifauna abundance values average ranged from 31.33-52.22 ind/m2.